Cancer‐Associated Fibroblasts: Heterogeneity, Cancer Pathogenesis, and Therapeutic Targets - Yutao Li; Qingyun Liu; Xilin Jing; Yuqi Wang; Xiaohua Jia; Xing Yang; Kezhong Chen (MedComm)
ABSTRACT Cancer‐associated fibroblasts (CAFs) are functionally diverse stromal regulators that orchestrate tumor progression, metastasis, and therapy resistance through dynamic crosstalk within the tumor microenvironment (TME). Recent advances in single‐cell multiomics and spatial transcriptomics have identified conserved CAF subtypes with distinct molecular signatures, spatial distributions, and context‐dependent roles, highlighting their dual capacity to promote immunosuppression or restrain tumor growth. However, therapeutic strategies struggle to reconcile this functional duality, hindering clinical translation. This review systematically categorizes CAF subtypes by origin, biomarkers, and TME‐specific functions, focusing on their roles in chemoresistance, maintenance of stemness, and formation of immunosuppressive niches. We evaluate emerging targeting approaches, including selective depletion of tumor‐promoting subsets (e.g., fibroblast activation protein+ CAFs), epigenetic reprogramming toward antitumor phenotypes, and inhibition of CXCL12/CXCR4 or transforming growth factor‐beta signaling pathways. Spatial multiomics‐driven combinatorial therapies, such as the synergistic use of CAFs and immune checkpoint inhibitors, are highlighted as strategies to overcome microenvironment‐driven resistance. By integrating CAF biology with translational advances, this work provides a roadmap for developing subtype‐specific biomarkers and precision stromal therapies, directly informing efforts to disrupt tumor‐stroma coevolution. Key concepts include spatial transcriptomics, stromal reprogramming, and tumor‐stroma coevolution, offering actionable insights for both mechanistic research and clinical innovation.